Investigation Skin Friction Reduction using Nano Bubble Injection on Flat Plates - Gunawan, Gunawan; Utomo, A. S. A.; Yanuar, Yanuar (Journal of Advanced Research in Micro and Nano Engineering, 2020)
The movement of objects in a solution will form a drag force. These obstacles occur because of the interaction between the object and the surface of the fluid. The interaction between fluid and matter is caused by the frictional force between the object within the boundary layer. Nevertheless, to overcome drag, a lubrication layer is needed as a divider between the fluid and a shifting object's exterior. The observation above about the reduction of skin resistance was carried out by air injection to produce a cavitation layer within the boundary layer that produced a nano-sized bubble. The drag reduction phenomenon was investigated in experimental tanks to see the interaction of 50 µm sized nanobubbles generated by carbon-ceramic tube on the surface of a 100 x 100 mm thick plate. This interaction is seen in the frictional force data on the plates captured by the load cell at a fluid velocity (U) 1 ms-1 to 20 ms-1 with 1 ms-1 interval. The effect of nanobubbles is seen when the gas distribution increases at medium fluid velocity 7 ms-1 < U < 13 ms-1. Significant contraction exists because the nanobubbles are concentrated on the plate's surface due to its low slip characteristics, resulting in a maximum drag reduction of 85% in a skin friction ratio of 0.4 < Cv < 0.6.